10-3(2x-7)=5(x+5)-6

Simple and best practice solution for 10-3(2x-7)=5(x+5)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-3(2x-7)=5(x+5)-6 equation:


Simplifying
10 + -3(2x + -7) = 5(x + 5) + -6

Reorder the terms:
10 + -3(-7 + 2x) = 5(x + 5) + -6
10 + (-7 * -3 + 2x * -3) = 5(x + 5) + -6
10 + (21 + -6x) = 5(x + 5) + -6

Combine like terms: 10 + 21 = 31
31 + -6x = 5(x + 5) + -6

Reorder the terms:
31 + -6x = 5(5 + x) + -6
31 + -6x = (5 * 5 + x * 5) + -6
31 + -6x = (25 + 5x) + -6

Reorder the terms:
31 + -6x = 25 + -6 + 5x

Combine like terms: 25 + -6 = 19
31 + -6x = 19 + 5x

Solving
31 + -6x = 19 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
31 + -6x + -5x = 19 + 5x + -5x

Combine like terms: -6x + -5x = -11x
31 + -11x = 19 + 5x + -5x

Combine like terms: 5x + -5x = 0
31 + -11x = 19 + 0
31 + -11x = 19

Add '-31' to each side of the equation.
31 + -31 + -11x = 19 + -31

Combine like terms: 31 + -31 = 0
0 + -11x = 19 + -31
-11x = 19 + -31

Combine like terms: 19 + -31 = -12
-11x = -12

Divide each side by '-11'.
x = 1.090909091

Simplifying
x = 1.090909091

See similar equations:

| -7(x+1)=13 | | y-4=4*(1+0) | | -2(x-4)=3x+6-1x | | 12=a/5-4 | | 13(x-1)=7x+23 | | 15x=18+13x | | 13y+36=153 | | 8(4s+9)=328 | | -3x-6/4=3 | | y^2-xy-3x=1 | | 1/6x-9=-2 | | 2x-21=5x-3y-12 | | (2x-7)+(3x+4)=0 | | 10x^4=0.001 | | (7/4)(-5) | | 15p+p+-19p+20p+-14p-16=-2 | | 8r+2r-2r-3r-3r=20 | | -5n-(-14n)+-11n+-4n=18 | | 2(x-4)-3(5x-1)=8 | | 7j+6j-12j=17 | | -13h+8h+10h=-20 | | -5x+4x=-20 | | (1-2a)x^2-2ax-1=0 | | 4x^2-29+5x+1=0 | | 9(6x+2)whenx=9 | | (8+i)(7+5i)=0 | | 2*m*n*8= | | 3x+12-5x+10=2x-5x+5 | | q^2-11q+30=0 | | -10x+30=-3x+100 | | 4/x-2=43 | | x^2-8x-15=3x-3 |

Equations solver categories